PROFIL KONDISI FISIK SISWA EKSTRAKURIKULER BOLA BASKET PUTRA SMA N 02 UNGARAN TAHUN 2012 (Department of Sports Science, Faculty of Sports Science, Universitas Negeri Semarang, 2014)
Tujuan penelitian ini adalah untuk mengetahui tingkat kondisi fisik siswa ekstrakurikuler bola basket putra SMA N 02 Ungaran tahun 2012. Populasi penelitian ini adalah seluruh siswa ekstrakurikuler bola basket putra SMA N 02 Ungaran tahun 2012 yang berjumlah 12 siswa. Sample yang digunakan dalam penelitian ini menggunakan total sampling. Berdasarkan hasil penelitian bahwa rata-rata skor tingkat kondisi fisik siswa ekstrakurikuler bola basket putra SMA N 02 Ungaran tahun 2012 adalah sebesar 2.65 yang termasuk dalam kategori kurang. Ditinjau dari tingkat kondisi fisik masing-masing siswa yaitu, 9 siswa (75%), selebihnya 3 siswa (25%) dalam kategori sedang. Simpulan dari hasil penelitian ini yaitu kondisi fisik siswa ekstrakurikuler bola basket putra SMA N 02 Ungaran tahun 2012 dalam kategori kurang.The purpose of this study was to determine the level of the physical condition of man’s basketball extraculicular of negeri 02 senior high school year 2012. The study population was all man’s basketball extraculicular of negeri 02 senior high school year 2012 totaling 12 people. The sample in this study uses total sampling. Based on the survey results revealed that the average score of the level of the physical condition of man’s basketball extraculicular of negeri 02 senior high school year 2012 is 2.65 which is included in the category less. Judging from the level of the physical condition of each athlete is known that most of the athletes, 9 studens (75%) in the category of less, the remaining 3 studens (25%) in the medium category. Conclusions from this research that the physical condition of man’s basketball extraculicular of negeri 02 senior high school year 2012 in the category of less.